2013
DOI: 10.1093/glycob/cwt019
|View full text |Cite
|
Sign up to set email alerts
|

The secondary cell wall polysaccharide of Bacillus anthracis provides the specific binding ligand for the C-terminal cell wall-binding domain of two phage endolysins, PlyL and PlyG

Abstract: Endolysins are bacteriophage enzymes that lyse their bacterial host for phage progeny release. They commonly contain an N-terminal catalytic domain that hydrolyzes bacterial peptidoglycan (PG) and a C-terminal cell wall-binding domain (CBD) that confers enzyme localization to the PG substrate. Two endolysins, phage lysin L (PlyL) and phage lysin G (PlyG), are specific for Bacillus anthracis. To date, the cell wall ligands for their C-terminal CBD have not been identified. We recently described structures for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 46 publications
4
26
0
Order By: Relevance
“…Measurement of dissociation constants for the cell wall binding domains of the endolysins PlyL and PlyG using surface plasmon resonance established a preferred interaction with a trisaccharide bearing the galactosyl moiety at C-4 of the nonreducing GlcNAc moiety (9). PlyL and PlyG were also found to interact with highly purified SCWP of several B. anthracis isolates via their C-terminal domains but not their Nterminal catalytic domains, thus corroborating the notion that the SCWP serves as a receptor for ␥ phage lysins (10).…”
Section: B Acillus Anthracis Elaborates the Secondary Cell Wall Polyssupporting
confidence: 52%
“…Measurement of dissociation constants for the cell wall binding domains of the endolysins PlyL and PlyG using surface plasmon resonance established a preferred interaction with a trisaccharide bearing the galactosyl moiety at C-4 of the nonreducing GlcNAc moiety (9). PlyL and PlyG were also found to interact with highly purified SCWP of several B. anthracis isolates via their C-terminal domains but not their Nterminal catalytic domains, thus corroborating the notion that the SCWP serves as a receptor for ␥ phage lysins (10).…”
Section: B Acillus Anthracis Elaborates the Secondary Cell Wall Polyssupporting
confidence: 52%
“…Plasmids expressing mCherry or its hybrids from the T7 promoter of pET16b included pJK81 (mCherry alone) as well as pJK87 and pJK88, which express the mCherry coding sequence fused to the 3= end of the coding sequence for the Sap or EA1 SLH domain, i.e., residues 30 to 210 (pSap SLH -mCherry and pEA1 SLHmCherry) (4,9). Plasmid pJK81 was digested with XhoI and ligated with the XhoI-restricted, PCR-amplified portion of plyG encoding the carbohydrate binding domain (amino acids 166 to 233 of PlyG [38]) to create pPlyG CBD -mCherry. All cloning steps were performed in E. coli DH5␣.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work demonstrated that bacteriophage lysins of B. anthracis, PlyG and PlyL, associate with the SCWP through their C-terminal cell wall binding domain (CBD) in a manner independent of csaB-mediated ketal-pyruvylation (38,(42)(43)(44). We generated purified PlyG CBD -mCherry, where the C-terminal CBD of PlyG (38) is fused to the mCherry reporter, to assess the overall abundance and subcellular distribution of the SCWP (with or without ketal-pyruvate) in wild-type and tagO::aad9(pts-tagO i ) vegetative forms.…”
Section: B Anthracis Tago::aad9(pts-tagomentioning
confidence: 99%
“…CBD binds to peptidoglycan ligands or secondary cell-wall polymers like teichoic acids and neutral polysaccharides Ganguly et al, 2013) found in the cell wall of the host bacterium. They are involved in positioning the catalytic domain for efficient cleavage of the peptidoglycan and confer some degree of 7 specificity to the enzyme (Loessner et al, 2002).…”
Section: Structure and Enzymatic Activity Of Endolysins And Vapghsmentioning
confidence: 99%
“…For example, amidases PlyG and PlyL selectively bind to secondary cell wall polysaccharides of the bacilli cell wall (Mo et al, 2012;Ganguly et al, 2013), and amidase Pal contains a choline binding module that attaches the enzyme to choline residues present in pneumococcal envelope (García et al, 1988). These conserved catalytic and binding targets have been suggested to contribute to the lack of bacterial resistance development against phage lytic proteins (Fischetti, 2005;Rodriguez-Rubio et al, 2013).…”
Section: Structure and Enzymatic Activity Of Endolysins And Vapghsmentioning
confidence: 99%